Penginjilan Kontekstual dalam Penggunaan Media Sosial untuk Menyebarkan Injil di Era Digital - Letlang, Adrianus (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
: In the rapidly growing digital era, social media plays an important role in communication and information delivery, including in evangelism according to the Great Commission of Jesus Christ. Digital technology enables churches to reach individuals who do not yet know Christ through various online platforms such as websites, YouTube, Facebook, and Instagram. This research aims to explore the utilization of social media in evangelism, as well as how digital technology enriches creativity and innovation in the delivery of the gospel message. The method used in this research is descriptive qualitative, by collecting data through interviews and observations of churches that use social media in evangelistic ministry. The results show that social media is a very effective tool in delivering the message of salvation and shaping a more just and harmonious society. However, there are challenges such as cultural differences and limited resources in utilizing technology to its full potential. In conclusion, digital evangelism through social media not only expands the reach of the church, but also has a positive impact on the spiritual and social lives of the global community.